2015
DOI: 10.1039/c4ce01717j
|View full text |Cite
|
Sign up to set email alerts
|

Tetrazoles: calcium oxalate crystal growth modifiers

Abstract: Metabolically stable tetrazole molecules are shown to impact calcium oxalate crystallization, thus tetrazoles can be used in investigating biological crystallization processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…As has been previously reported 15 , tetrazoles have been found to change the morphology of COM crystals but seemingly through different mechanisms of interaction than their carboxylic acid equivalent counter-parts. This manuscript looks at understanding the interactions with similarly sized molecules as shown in Figure 1, with emphasis on the adsorption of the molecules to the crystal.…”
Section: Crm Investigation Of Com In the Presence Of Cgm'ssupporting
confidence: 58%
See 1 more Smart Citation
“…As has been previously reported 15 , tetrazoles have been found to change the morphology of COM crystals but seemingly through different mechanisms of interaction than their carboxylic acid equivalent counter-parts. This manuscript looks at understanding the interactions with similarly sized molecules as shown in Figure 1, with emphasis on the adsorption of the molecules to the crystal.…”
Section: Crm Investigation Of Com In the Presence Of Cgm'ssupporting
confidence: 58%
“…Recently researchers have been utilising the bioisostere nature of carboxylic acids and tetrazoles [9][10][11][12][13] to investigate the effect the tetrazole moiety has in medicine, and more recently in the field of crystal growth modification. Before our group started investigating tetrazoles as modifiers, they had not been used as crystal growth modifiers; now crystal systems have been investigated including, barium sulfate, calcium carbonate 14 , and calcium oxalate 15 , all of which were discovered to be inhibited by the presence of tetrazoles during crystallisation. The tetrazole species used in this study are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…As a functional group, tetrazoles have found widespread use in the design of molecular species for diverse applications, including medicinal chemistry, coordination polymers, crystal growth inhibition and luminescent materials . Tetrazoles are five‐membered aromatic heterocycles possessing four adjacent N atoms.…”
Section: Introductionmentioning
confidence: 99%
“…7 Incorporation of the additive is also possible, where the additive is internal to the crystal resulting in an altering in the crystal's behaviour and growth. There has already been some research into the use of crystal growth modifiers for the control of the formation of kidney stones, 8–21 although many of the studies investigate the impact in simple solutions unrelated to real life conditions.…”
Section: Introductionmentioning
confidence: 99%